A comparative assessment of migrant and indigenous entrepreneurs on regional development: A case of Odisha, India. (7th December 2021) - Sarangi, Subrat; Renin Singh, R. K.; Kar, Brajaballav
Abstract: The paper aims to compare the relative influence of migrant and indigenous entrepreneurs on regional development in the eastern state of Odisha in a developing country like India. The data is based on ownership across 30 districts and ten different sectors for small and medium businesses. It is modeled on economic indicators such as Net District Domestic Product (NDDP) and employment generation at the district level. One‐way ANOVA and multiple linear regression on the data set suggest that ownership pattern influences development indices differently, hence having policy‐level implications based on the goals to be achieved. While migrant entrepreneurs' impact NDDP and employment opportunities positively for main workers, indigenous entrepreneurs from Odisha positively influence employment opportunities at an overall level, and for marginal workers, everything else remains unchanged. Hence, during slowdowns or post‐pandemic recovery situations, when the need of the hour for the local government is immediate employment and livelihood for low‐skill‐based marginal workers, facilitating indigenous owners is more preferred.